Endolithic Bacterial Diversity in Lichen-Dominated Communities Is Shaped by Sun Exposure in McMurdo Dry Valleys, Antarctica - Mezzasoma, Ambra; Coleine, Claudia; Sannino, Ciro; Selbmann, Laura (Microbial Ecology, 2021)
The diversity and composition of endolithic bacterial diversity of several locations in McMurdo Dry Valleys (Continental Antarctica) were explored using amplicon sequencing, targeting the V3 and V4 of the 16S region. Despite the increasing interest in edaphic factors that drive bacterial community composition in Antarctic rocky communities, few researchers focused attention on the direct effects of sun exposure on bacterial diversity; we herein reported significant differences in the northern and southern communities. The analysis of β-diversity showed significant differences among sampled localities. For instance, the most abundant genera found in the north-exposed rocks were Rhodococcus and Blastococcus in Knobhead Mt.; Ktedonobacter and Cyanobacteria Family I Group I in Finger Mt.; Rhodococcus and Endobacter in University Valley; and Segetibacter and Tetrasphaera in Siegfried Peak samples. In south-exposed rocks, instead, the most abundant genera were Escherichia/Shigella and Streptococcus in Knobhead Mt.; Ktedonobacter and Rhodococcus in Finger Mt.; Ktedonobacter and Roseomonas in University Valley; and Blastocatella, Cyanobacteria Family I Group I and Segetibacter in Siegfried Peak. Significant biomarkers, detected by the Linear discriminant analysis Effect Size, were also found among north- and south-exposed communities. Besides, the large number of positive significant co-occurrences may suggest a crucial role of positive associations over competitions under the harsher conditions where these rock-inhabiting microorganisms spread. Although the effect of geographic distances in these extreme environments play a significant role in shaping biodiversity, the study of an edaphic factor, such as solar exposure, adds an important contribution to the mosaic of microbial biodiversity of Antarctic bacterial cryptoendolithic communities. no